2015
DOI: 10.1051/mmnp/201510609
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Speeds and Linear Determinacy for Two Species Competition Systems with Nonlocal Dispersal in Periodic Habitats

Abstract: Abstract. The current paper is concerned with the existence of spreading speeds and linear determinacy for two species competition systems with nonlocal dispersal in time and space periodic habitats. The notion of spreading speed intervals for such a system is first introduced via the natural features of spreading speeds. The existence and lower bounds of spreading speed intervals are then established. When the periodic dependence of the habitat is only on the time variable, the existence of a single spreading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Throughout this paper, we assume (H0). The following results on the persistence, coexistence, and extinction in (1.1) have been proved in literature (see, for example, [10], [18], [21]).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Throughout this paper, we assume (H0). The following results on the persistence, coexistence, and extinction in (1.1) have been proved in literature (see, for example, [10], [18], [21]).…”
Section: Introductionmentioning
confidence: 82%
“…See [1,4,5,6,7,8,10,12,13,14,15,19,24,25], etc. for the case that Au = u xx and see [2,6,9,18,20,21], etc. for the case Au(t, x) = R κ(y − x)u(t, y)dy − u(t, x).…”
Section: Introductionmentioning
confidence: 99%
“…For monotone semiflows of bistable type, Fang and Zhao [9] interpreted the bistability from a monotone dynamical system point of view to find a link between the monostable subsystems and bistable system itself, which is used to establish the existence of bistable wavefronts. We refer to [21,6,34,35] for nonlocal dispersal equations, and two survey papers [43,15] for more references. There are also quite a few investigations on time-periodic fronts of reaction-diffusion equations, see, e.g., [1,2,10,26,46,47,45] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…For a reaction-diffusion competition model with seasonal succession, Ma and Zhao [26] studied the existence of single spreading speed and its linear determinacy, and showed that the spreading speed coincides with the minimal wave speed of time-periodic traveling waves. More recently, Kong, Rawal and Shen [21] proposed a competition model with nonlocal dispersal in a time and space periodic habitats, and investigated the spreading speed and its linear determinacy. For traveling waves in a time-delayed reaction-diffusion competition model with nonlocal terms, we refer to Gourley and Ruan [13].…”
Section: Introductionmentioning
confidence: 99%
“…Behavior of solutions near the stability boundary is studied using the techniques of weakly nonlinear analysis. The spreading speed in the system of competition of species with nonlocal dispersion is estimated in [26]. Pattern formation in the system of competition of species with nonlocal consumption is studied in [10].…”
Section: About This Issuementioning
confidence: 99%